Analisis Pemanfaataan Webqual 4.0 Dan Customer Satisfaction Index (CSI) Dalam Menilai Kualitas Website Terhadap Kepuasan Pelanggan Pada Aplikasi Tokopedia - Fikri, Muhammad; Herawati, Sri; Negara, Yudha Dwi Putra (Universitas Muhammadiyah Ponorogo, 2024)
Tokopedia's website is declining because customers complain about Tokopedia's service quality. The improvement of website services aims to increase the ranking and user satisfaction of the Tokopedia website has not yet achieved optimal results. With this, research was conducted to analyse the use of Webqual 4.0 and Customer Satisfaction Index (CSI) in assessing the quality of the website on customer satisfaction on the Tokopedia application. From the results of the Validity Test of the level of importance and satisfaction, the r table which has a significance level of 0.05 with respondents as many as 100 people is 0.1966. The results of the calculated r value r table value as a result the entire attribute is valid and can be used in research and the results of the Reliability Test of interests and satisfaction are worth Cronbach's Alpha 0.6 (Reliable requirement value), as a result the questionnaire can be declared Reliable. From the results of the CSI calculation, a value of 80.4% was obtained. The CSI value obtained lies in the 66% - 80.99% index with the description